Comparative Genomic Analysis of TCP Genes in Six Rosaceae Species and Expression Pattern Analysis in Pyrus bretschneideri - Zhao, Yu; Su, Xueqiang; Wang, Xinya; Wang, Mengna; Chi, Xujing; Aamir Manzoor, Muhammad; Li, Guohui; Cai, Yongping (Frontiers in Genetics, 2021)
TCP (TEOSINTEBRANCHEDI, CYCLOIDEA, PROLIFERATING CELL FACTORI) family is a unique transcription factor in plants, which plays an important role in the development of plant leaf shape and flower symmetry. In this study, comparative genomics analysis was performed on six species of Rosaceae (Fragaria vesca, Malus domestica, Prunus mume, Pyrus bretschneideri, Rubus occidentalis, Prunus avium). We identified a total of 155 genes: 34 in Pyrus bretschneideri, 19 in Fragaria vesca, 52 in Malus domestica, 19 in Prunus mume, 17 in Rubus occidentalis, and 14 in Prunus avium. Through systematic evolution analysis, conservative sequence analysis, chromosome location analysis, reveal the evolution of 6 species of Rosaceae. Analysis of the expression levels of Chinese white pear fruits at different development stages and different tissues found that PbTCP10,19,22 may be related to flower development, and TCP14,23,24,30 may be involved in the formation of lignin in pear fruits. The results of subcellular localization showed that PbTCP mainly functions in the nucleus.In summary, TCP family members are very conservative in the evolution of Rosaceae species, and play an important role in the development of Chinese white pear flowers and fruit.